2017
DOI: 10.1111/bjd.15802
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to biological therapies during conception and pregnancy: a systematic review

Abstract: Summary Background Biological therapies are effective treatments for psoriasis and are often prescribed to women of child‐bearing age. Objectives To evaluate the safety of biological therapy in conception and/or pregnancy. Methods We performed a systematic review of PubMed, MEDLINE, Embase and Cochrane databases for multivariate‐adjusted studies of women exposed to biologics relevant to the treatment of psoriasis during conception and/or pregnancy. Results We identified four population‐based cohort studies inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 31 publications
0
22
0
3
Order By: Relevance
“…This data-quality discussion may apply to studies on other diseases, and the authors cite examples of successful disease pregnancy registries for other conditions. An unrelated research group advocated for a disease registry as the best-positioned design to collect information on the preconceptional course and severity of underlying chronic inflammatory diseases for studies on drug safety in pregnancy [17]. On the other hand, another group of researchers expressed the need for an international multiproduct pregnancy exposure registry for monoclonal antibodies for any indication [18]; this registry would include some but not all treatments for MS. Our group conducted a literature review that identified studies on the safety of MS treatments in pregnancy and identified 43 publications from product-specific pregnancy exposure registries, disease registries, database studies and studies with other approaches [19].…”
Section: Results From Pregnancy Exposure Registries and Database Studiesmentioning
confidence: 99%
“…This data-quality discussion may apply to studies on other diseases, and the authors cite examples of successful disease pregnancy registries for other conditions. An unrelated research group advocated for a disease registry as the best-positioned design to collect information on the preconceptional course and severity of underlying chronic inflammatory diseases for studies on drug safety in pregnancy [17]. On the other hand, another group of researchers expressed the need for an international multiproduct pregnancy exposure registry for monoclonal antibodies for any indication [18]; this registry would include some but not all treatments for MS. Our group conducted a literature review that identified studies on the safety of MS treatments in pregnancy and identified 43 publications from product-specific pregnancy exposure registries, disease registries, database studies and studies with other approaches [19].…”
Section: Results From Pregnancy Exposure Registries and Database Studiesmentioning
confidence: 99%
“…Until recently, there has been no clear evidence found of increased adverse pregnancy and birth outcome in women with psoriasis [ 10 ]. Unfortunately, these studies did not stratify for drug use, thus the effect of medication on pregnancy outcomes were not considered [ 7 , 10 ].…”
Section: Psoriasis and Pregnancymentioning
confidence: 99%
“…Most TNFi safety studies have been conducted in indirect populations, such as women with IBD and rheumatoid arthritis, consequently no studies specifically address TNFi potential risk of harm in pregnant women with psoriasis or the outcomes in their infants [ 7 ].…”
Section: General Safety Of Tnf Inhibitors During Pregnancymentioning
confidence: 99%
See 2 more Smart Citations